Making Louis Agassiz’s wish come true: combining forces and a new protocol for collecting comparative skeletal material of sharks, skates and rays, as a comment and an addition to ‘The need of providing tooth morphology in descriptions of extant elasmobranch species’ by Guinot et al. (2018) - Mollen, Frederik H. (Zootaxa, 2019)
Palaeoichthyologist G. Guinot and colleagues (Guinot et al., 2018) are correct to request that new species descriptions of extant sharks, skates and rays include information on tooth morphology. But, even if their request is heeded, it will not address the broader issue associated with taxa that have been poorly described or incompletely illustrated in the past.